Sharia Financing Online Education: Mudhorobah, Musyarokah and Murobahah Financing - Sukma Amelia Khaerani; Fira Rakhmatika Pohan; Rauzhatu Sakinah Gustia (FEBI UIN Sunan Kalijaga Yogyakarta, 2023)
The word financing comes from the word